Inadvertent radical nephrectomy leads to worse prognosis in renal pelvic urothelial carcinoma patients: A propensity score-matched study - Wu, Feixiang; Zhang, Pan; Li, Lingxun; Lin, Shiqing; Liu, Jianhong; Sun, Yi; Wang, Yuanlong; Luo, Chengjun; Huang, Yu; Yan, Xiao; Zhang, Meng; Liu, Guixi; et al. (Frontiers in Oncology, 2022)
Objective: To compare the overall survival (OS) and cancer-specific survival (CSS) in renal pelvic urothelial carcinoma (RPUC) patients treated with radical nephroureterectomy (NU) and inadvertent radical nephrectomy (RN). Patients and methods: In this retrospective study, patients with RPUC underwent NU or RN diagnosed between 2004-2017 were identified from the Surveillance, Epidemiology, and End Results database. To adjust the confounders, the propensity score-matched analysis was conducted. The Kaplan–Meier method and log-rank test were performed to explore the effect of different surgical methods on OS and CSS. Results: A total of 2197 cases were finally included in this analysis. Among which, 187 (8.5%) patients treated with RN and 2010 (91.5%) patients treated with NU. Before matching, the survival analysis revealed that the OS (HR: 1.444, 95%CI: 1.197, 1.741) and CSS (HR: 1.522, 95%CI: 1.211, 1.914) of patients received RN were worse than that of patients received NU (P=0.0001 and P=0.0003, respectively). After matching, the RN group has a worse OS (HR: 1.298, 95%CI: 1.002, 1.682) than NU group (P=0.048). No significant difference was observed in CSS between RN and NU group (P=0.282). The hierarchical analysis showed that there was no significant difference was observed in OS and CSS in patients with tumor size ≤4.2cm (P= 0.884 and P= 0.496, respectively). In tumor size >4.2cm, both OS (HR: 1.545, 95%CI: 1.225, 1.948) and CSS (HR: 1.607, 95%CI: 1.233, 2.095) of patients received RN were worse than that of patients received NU (P= 0.0002 and P= 0.0005). Conclusion: RN could lead to worse oncological outcomes than NU in patients with renal pelvis urothelial carcinoma. Accurate diagnosis of renal pelvis urothelial carcinoma is extremely important.